The Second Kummer Function with Matrix Parameters and Its Asymptotic Behaviour - Georg Wehowar; Erika Hausenblas (Abstract and Applied Analysis)
In the present article, we introduce the second Kummer function with matrix parameters and examine its asymptotic behaviour relying on the residue theorem. Further, we provide a closed form of a solution of a Weber matrix differential equation and give a representation using the second Kummer function.